Minimum Wages for Domestic Workers: Impact Evaluation of the Indian Experience - Rohan Ravindra Gudibande; Arun Jacob (Global Labor Organization (GLO), 2018)
The paper explores the labor market effect of minimum wage legislations in the informal sector for a developing country. The paper conducts an impact evaluation of the minimum wage legislation for domestic workers introduced in four states in India over the period of 2004-2012. Combining matching procedures with difference-in-difference, the paper estimates both the short-run and the long-run impact of the legislation on real wages and employment opportunities. Results show a positive impact of the legislation on real wages in the short-run, with no significant impact in the long-run. Further, the legislation did not seem to have had any impact on the extensive margin in terms of employment opportunities or the probability of being employed as a domestic worker over the entire period. Available evidence, in line with theoretical predictions, point towards a weak enforcement of the legislation as the driving factor of observed results.
Keywords: J16; J31; J33; J38; 330; wages; minimum wages; domestic workers; unemployment; informal sector